Techno-Economic Comparison of Electrochemical Batteries and Supercapacitors for Solar Energy Storage in a Brazil Island Application: Off-Grid and On-Grid Configurations - Alex Ximenes Naves; Gladys Maquera; Assed Haddad; Dieter Boer (My University, 2025)
The growing concern for energy efficiency and the increasing deployment of intermittent renewable energies has led to the development of technologies for capturing, storing, and discharging energy. Supercapacitors can be considered where batteries do not meet the requirements. However, supercapacitors in systems with a slower charge/discharge cycle, such as photovoltaic systems (PVS), present other obstacles that make replacing batteries more challenging. An extensive literature review unveils a knowledge gap regarding a methodological comparison of batteries and supercapacitors. In this study, we address the technological feasibility of intermittent renewable energy generation systems, focusing on storage solutions for PVS energy. We propose a framework according to one of the essential parameters for their application in PVS: Energy Density or Specific Energy (Wh/kg). Through computational modelling, issues related to the intermittency and seasonality of the solar energy source are addressed, evaluating the possible benefits of implementing batteries, supercapacitors, and hybrid solutions in renewable energy generation systems. Also, the characteristics of two hypothetical configurations of photovoltaic systems, off-grid and on-grid, were analysed. This analysis highlights the characteristics of totally isolated systems (e.g., on an island or remote village) and systems connected to the grid (e.g., solar farms), where eliminating the use of batteries can bring significant benefits, in addition to tax incentives, which are decisive in the investment decision-making process. The results clarify the viability of PVS and allow an understanding of parameters that can support the technical decision process between isolated or non-isolated systems, reflecting economic and financial issues.
Keywords: Supercapacitor; Energy storage; Grid; Electrochemical energy storage; Environmental science; Environmental economics; Renewable energy; Photovoltaic system; Electrical engineering; Grid energy storage; Electrochemical energy conversion; Process engineering; Electrochemistry; Automotive engineering; Engineering; Distributed generation; Materials science; Power (physics); Geography; Economics; Chemistry; Physics; Electrode; Geodesy; Quantum mechanics; Physical chemistry; Supercapacitor; Energy storage; Grid; Electrochemical energy storage; Environmental science; Environmental economics; Renewable energy; Photovoltaic system; Electrical engineering; Grid energy storage; Electrochemical energy conversion; Process engineering; Electrochemistry; Automotive engineering; Engineering; Distributed generation; Materials science; Power (physics); Geography; Economics; Chemistry; Physics; Electrode; Physical Sciences Materials Science Electronic, Optical and Magnetic Materials Supercapacitor Materials and Fabrication; Physical Sciences Engineering Automotive Engineering Advanced Battery Technologies Research; Physical Sciences Engineering Control and Systems Engineering Microgrid Control and Optimization